Personal determinants of change agents' decision-making behavior in community health promotion: a qualitative study - Lisa Paulsen; Lea Benz; Christina Müller; Birgit Wallmann-Sperlich; Jens Bucksch (BMC, 2023)
Abstract Background Implementing environmental changes to promote healthier communities requires initial positive decisions by change agents from local politics and government. However, there is little research on what influences the change agents' decisions. This explorative, qualitative study aims to identify the personal determinants of the decision-making behavior of local change agents. Methods We conducted semi-structured interviews to assess the personal determinants of decision-making behavior among 22 change agents from local politics and government. Relevant determinants were identified through a structured content analysis of the interview transcripts using the software MAXQDA 2020. Results We found the following seven essential clusters of personal determinants of the decision-making behavior of change agents from local politics and government: Imprinting, socialization, and biography; experiences and involvement; attitudes and outcome expectations towards important issues and aspects; knowledge; emotions; personal benefits; and the perceived influences of others. Conclusions The identified personal determinants might serve as a source of understanding the decision-making behavior of change agents in community decision-making processes. Our findings can contribute to the effective planning and implementation of evidence-based multilevel interventions related to changing environmental conditions in communities and provide important information on which personal determinants should be considered when derive strategies for community health promotion within a systematic approach of developing an intervention program theory.